Analysis of Electronic Payment Systems in Ghana - A Case Study of Mobile Payment System - Kwadzo, Francis Agbenyegah; Adroe, Regina Kafui; Asante, Dr. Michael (International Journal of Scientific Research and Management (IJSRM), 2018)
Mobile payment is an electronic payment made through a mobile device. As the number of mobile phone subscribers in Ghana increases, so does the market for mobile money services. The majority of Ghanaians lack any formal bank account. An estimated 80 percent of Ghanaians are “unbanked” – meaning they conduct their transactions outside the banking sector with no access to financial services. Products like “mobile money,” that enable safe and secure money transfers without the use of a bank account, could have a major impact on this unserved segment of the population. Mobile money gives anyone with a mobile phone the ability to transfer money, make cash payments and conduct other financial transactions over the phone. Currently, there are four mobile money payment systems in Ghana, namely, MTN mobile money, Vodafone (VF) cash, Tigo cash and Airtel money. For an effective operation of these systems, Privacy, Traceability, Cost of Transaction, and Simplicity of the Processes involved are of much interest. The study examined the loopholes in the current mobile payment systems and proposed a framework to address the loopholes such as: Entering of information on next of kin into the system during registration, acceptance of year of birth as PIN, transactional PIN decrypted, no entering of a Valid ID number into the system, no provision for security word during token cash out, no provision for guarantor information, no provision for BoG permit number, no provision for police clearance number, and data in transit not encrypted. Keywords: Transactions, mobile money, traceability